English for Secretarial Program: Target and Learning Needs of 'Cinta Kasih Tzu Chi' Vocational School Students - Junita Junita; Nurdiana Nurdiana (Universitas Bunda Mulia, 2019)
English is one of compulsory subjects in vocational high schools. It is a required school subject as students of vocational school graduates are prepared to work based on their major and skills. In addition, in the workplace context, English is the common foreign language used in and among divisions in the workplace. To help the students use the language appropriately, schools need to prepare them with adequate learning materials. Thus, reliable sources of learning, one of which is English coursebooks, should incorporate appropriate language input for the students specifically devised for vocational school students. Unfortunately, most of the coursebooks contain materials which do not meet target and learning needs of the students who study in vocational schools. Therefore, this study aimed at examining their target and learning needs of English, particularly for those taking secretarial program. In order to achieve the objective of the study, a questionnaire consisting of target and learning needs items was distributed to the subjects of the research. The findings of this research revealed that the target needs of the students who majored in the secretarial program are to be able to communicate in English both in oral and written texts, vocabulary enhancement related to the workplace, and to pass the national exam. As for the learning needs, most of the students are keen on learning English from authentic materials integrated in all language skills.Keywords: materials development, target and learning needs, ESP